(untitled) - Sanders, Ralph (Westport, Conn, 1983)
Contents: International Context of Technology; The Past: Technological Dimensions of World History; The Present: Concepts and Circumstances; The Present: Institutions and Processes
Keywords: Đổi mới công nghệ,International relations,Technological innovations,Quan hệ quốc tế; Khía cạnh chính trị,Political aspects